The Effect Of Orthodontic Bonding Systems And Acidic Soft Drinks On Microleakage Using Confocal Laser Scanning Microscopy : An In-Vitro Study - Mahmoud, Belal Khaled (2011)
Enamel decalcification around and under the bracket base is a considerable problem. Microleakage under the orthodontic brackets increases the risk of decalcification and caries. There is a lack of information about microleakage that may occur under the orthodontic bracket when different types of adhesive are used and how it is affected by acidic soft drinks.